Description of Parent's Knowledge About Bias Immunization for Grade 1 and 2 Students at MI Al Irsyad Kediri City - Erna Rahmawati; Angraini Dyah Setyarini (Journal of Global Research in Public Health, 2024)
Immunization is one of the government's efforts to strengthen children's immunity and prevent millions of deaths and disabilities. Vaccination is carried out in primary schools, especially grades I and II, as a program of community health centers under the BIAS format. (Student Immunization Month) takes place in the form of measles vaccination in August and tetanus DT (Diphtheria) vaccination in November. Parental knowledge plays a very important role in implementing the program  BIAS vaccination, so that children do not get diseases that can be prevented by vaccination. The purpose of this study was to descriptively analyze parents' knowledge of BIAS vaccination in grade 1 and 2 students at MI Al Irsyad, Kediri city. This type of research used a quantitative descriptive method with a total of 64 respondents using a simple random sampling technique. Data collection in this study used questionnaires. The analysis used was a univariate analysis. Result of the univariate analysis showed that the highest level of parental education was high school with 39 respondents (60.9%), the type of work most respondents did was housewife with 21 respondents (32.8%), and a good level of knowledge for 28 respondents (44). %).Conclusion was that parental knowledge about BIAS immunization was quite good, in this case it can be seen from the results that 28 respondents (44%) had parental knowledge.